An Error Analysis in Writing English Essay at Junior High School - julia husna; Nuzulul Isna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Writing essay text is still difficult for most students at SMA Negeri 5 Aceh Barat Daya students. This study aims to analyze the errors made by students in their essay writing. This study conducted quantitative research. The test was given to 53 students as a technique of data collection. The result of the study showed that there were 582 total errors made by students. The errors are classified into 25.8% errors of subject-verb agreement, 20.6% errors of pronouns, 19.2% errors of adverbs, 17.2% errors of nouns, and 17.2% errors of simple present tense. The most prevalent error was subject-verb agreement because most students made a mistake pairing subjects with verbs.